AUTOBIOGRAPHY VS PHOTOGRAPHY AND MEMOIR VS CARICATURE AS FORMS OF PRESERVING THE AUTHOR’S MEMORY (DMITRY S. MEREZHKOVSKY) - Аlexey А. Kholikov (Studia Litterarum)
The essay focuses on visual images as one of the means of the writer’s reception on the example of such forms of preserving memory about Dmitry S. Merezhkovsky as autobiography and photography, on the one hand, and memoir and caricature, on the other. Photographic image comes close to autobiography in the following aspects. First, there is a functional affinity between these two forms, a verbal one and a visual one: both share the desire for authenticity. At the same time, photography as autobiography has not just documentary potential: photographic image is equally capable of reproducing and of reducing or distorting reality. Finally, photography (and this is its another affinity with a documentary genre) presents not only individual and personal but also cultural and historical interest. Between caricature and memoir — another pair of media preserving verbal and visual memory about the writer — there are overlaps as well. These “spaces” of memory have bigger potential for interpretation of the image than photography or autobiography. I prove this point by analyzing specific details that were emphasized by caricatures and memoirs of Merezhkovsky. At the same time, I argue that caricature as a visual “space” of memory is not self-sustained the same way photography and portrait are. The other aspect the essay is concerned with the elements of the memory about the writer that remain untranslatable into visual language. Methodologically, the essay relies on the works by N.I. Zhinkin, Y.N. Tyanyanov, Y.M. Lotman, R. Barthes, and S. Sontag.